Stress of stoicism: Low emotionality and high control lead to increases in allostatic load. Issue 4 (1st October 2016) - Doan, Stacey N.; Dich, Nadya; Evans, Gary W.
ABSTRACT: The present longitudinal study examined the combined effects of task persistence and negative emotionality (NE) on allostatic load (AL), a physiological indicator of chronic stress. In line with John Henryism theory, we hypothesized that high persistence combined with low NE may be indicative of a high-effort coping style, leading to high arousal of the nervous system and, as a consequence, increased AL. Mothers reported on children's NE ( N = 158, 72 females) at age 9. Persistence was measured at age 9 using a behavioral measure assessing persistence on an impossible task. AL was measured at ages 9 and 17. The AL measure captured hypothalamic pituitary adrenal axis, sympathetic adrenal medullary system, cardiovascular, and metabolic activity. Consistent with previous research, persistence protected against high AL in the context of high NE. However, combined with low NE, high behavioral persistence was associated with higher physiological stress. Our results have implications for both clinical and intervention contexts.